PERAMALAN KEBUTUHAN JUMLAH VAKSIN IMUNISASI CAMPAK DENGAN METODE SINGLE EXPONENTIAL SMOOTHING PADA PUSKESMAS MAYOR UMAR DAMANIK TANJUNGBALAI - Agi Septi Pitaya; Dr. William Ramdhan; Abdul Karim Syaputra (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2024)
Abstract: Major Umar Damanik Tanjungbalai Health Center, which is located on Jl. Mayor Umar Damanik, Pantai Burung Subdistrict, South Tanjungbalai, plays a role as part of regional autonomy efforts in providing health services to the community. Every week, the Community Health Center routinely holds a special immunization program for measles which is considered a general need. However, because of the important role of vaccines in improving children's health and preventing the transmission of measles, it is important to ensure the availability of vaccines every month. Currently, demand for measles vaccine at the Mayor Umar Damanik Tanjungbalai Health Center is still not optimal. There is still often an excess of vaccine stock which causes accumulation in storage areas, increasing the risk of vaccine expiration and a shortage of measles vaccine stock for children if the number of immunization vaccines is reduced. The inability to calculate vaccine needs causes errors in estimating the amount needed. As a result, vaccine stocks are currently unstable. To overcome this problem, a forecasting system is needed to calculate vaccine stocks in the coming months. Forecasting approaches, such as the Single Exponential Smoothing (SES) method, can be an effective solution for maintaining vaccine stock stability.Keywords: Amount of Measles Immunization Vaccine; SES Method.Abstrak: Puskesmas Mayor Umar Damanik Tanjungbalai, yang berlokasi di Jl. Mayor Umar Damanik Kelurahan Pantai Burung, Tanjungbalai Selatan, berperan sebagai bagian dari upaya otonomi daerah dalam memberikan pelayanan kesehatan kepada masyarakat. Setiap minggu, Puskesmas tersebut secara rutin menyelenggarakan program imunisasi khusus untuk campak yang dianggap sebagai kebutuhan umum. Namun, karena pentingnya peran vaksin dalam meningkatkan kesehatan anak dan mencegah penularan penyakit campak, penting untuk memastikan ketersediaan vaksin setiap bulannya. Saat ini, permintaan vaksin campak di Puskesmas Mayor Umar Damanik Tanjungbalai masih belum optimal. Masih sering terjadi kelebihan stok vaksin yang menyebabkan penumpukan di tempat penyimpanan, meningkatkan risiko kadaluwarsa vaksin dan kekurangan stok vaksin campak untuk anak jika jumlah vaksin imunisasi dikurangi. Ketidakmampuan dalam melakukan perhitungan kebutuhan vaksin menyebabkan kesalahan dalam memperkirakan jumlah yang diperlukan. Akibatnya, stok vaksin saat ini belum stabil. Untuk mengatasi masalah ini, diperlukan sistem peramalan untuk menghitung stok vaksin di bulan-bulan mendatang. Pendekatan peramalan, seperti metode Single Exponential Smoothing (SES), dapat menjadi solusi efektif untuk menjaga stabilitas stok vaksin.Kata Kunci : Jumlah Vaksin Imunisasi Campak; Metode SES